Tendencje zmian w organizacji skupu surowca w przemyśle cukrowniczym - Gonet, Danuta (Trends of Changes in Organization of Purchasing Raw Material for Sugar Industry, 2005)
The paper presents chosen elements influencing the purchasing centre in the sugar factory "Strzelin" SA between 1999 and 2003. It describes changes in the organization of the purchasing centre to reduce costs of sugar production.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 267-271